The Role of International Economic Law in Africa - Obale, Offah Ako (Society of International Economic Law (SIEL) Inaugural Conference 2008, 2008)
International Economic law (IEL) has a specific role to play in a complex modern Africa. The underdeveloped state of trade law regimes in Africa is arguably a reflection and product of the low level of commercial activity. The reverse is equally true in that underdevelopment in commercial activity on the continent is a reflection and product of the minimal role played thus far by international economic law.
Keywords: AEC; Africa; African; African Economic Community (AEC); Doha; Globilisation; International Economic Law; OHADA; Trade law; WTO